1949
DOI: 10.1021/ac60030a022
|View full text |Cite
|
Sign up to set email alerts
|

Estimation of Moisture in Sweet Potato Starch

Abstract: Acetic acid is not a product of the acid-dichromate oxidation of cellulose.Accurate cellulose analysis can be accomplished by the use of an experimental milliequivalent weight, 6.861 mg., based on the observed relative amounts of carbon monoxide and carbon dioxide formed during the acid-dichromate oxidation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

1950
1950
2013
2013

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 15 publications
0
3
0
Order By: Relevance
“…[1][2][3][4][5][6] Digital and personal computers, followed by the Internet and the World Wide Web have naturally strengthened this long-standing tradition. Today, it has become trivial to write that computers are everywhere and that they can take up an ever-increasing part of a worker's daily burden.…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3][4][5][6] Digital and personal computers, followed by the Internet and the World Wide Web have naturally strengthened this long-standing tradition. Today, it has become trivial to write that computers are everywhere and that they can take up an ever-increasing part of a worker's daily burden.…”
Section: Introductionmentioning
confidence: 99%
“…Except in the case of casein and peanut kernels, good agreement was observed with values obtained by drying in vacuo over magnesium perchlorate. A rapid (7-minute) method, suitable for plant control work, has been reported for moisture in sweet potato starch and other particulate materials (4). The specific gravity of the particles is determined psychometrically in large samples ranging in moisture content from 15 to 50%.…”
Section: Moisturementioning
confidence: 99%
“…Bainbridge et al (4), having found the British Standard Specification 1016 (1942) method and apparatus for distilling water from a 2-pound sample of coal by use of a petroleum distillate to be very lengthy when used for a brown coal with a high moisture content, developed a method and apparatus which greatly reduce the time, are equally precise with the British standard apparatus, and are more pleasant to work with.…”
Section: Proximate Analysismentioning
confidence: 99%